Design exploration with stochastic models of variation: Comparing two examples from facade subdivision - Datta, Sambit (Chinese University of Hong Kong, 2013)
The imitation of natural processes in architectural design is a long-standing area of research in computational design. The approach of “directed randomness” permits the stochastic exploration of a vast space of design possibilities. Stochastic methods are well developed in mathematical biological and the physical sciences and their application in architectural design is beginning to emerge as a new area of investigation. This paper presents two examples of modelling design exploration using stochastic models of variation. A stochastic model of design exploration is one where a system’s subsequent states are determined by a combination of the process’s predictable actions and by a random element. The random element may be the function of either an algorithm or human intervention. The behaviour of a stochastic process is therefore inherently non-deterministic. The paper discusses two stochastic process models, one based on wind motion and the second based on rotation. The stochastic model based on wind motion is applied to a facade subdivision problem to generate a vast space of possible panel configurations. The model of stochastic rotation is applied to a moveable panel facade based on pentagonal tiling. The models combine known parameters such as number and spacing of elements with an uncertain stochastic variable, wind direction and velocity in the case of one example and 2D and 3D rotation in the second example. The paper concludes with a discussion on a need to make an explicit allowance for uncertainty.